Fluidities and Fixities: Examining the Alignment of Digital Platforms Within Nairobi's Heterogeneous Infrastructural Configurations - Chambers, Joseph (Frontiers in Sustainable Cities, 2019)
Across the Global South, digital platforms have become increasingly present in the understanding, management and operation of cities and their infrastructures. In examining the impact of digital platforms within urban infrastructures however, the experiences of cities of the South, and especially informal urban settlements, remains significantly overlooked when considering the impact of digital technologies on urban processes. With digital technologies and associated platforms becoming ever more embedded within the infrastructures of informal settlements, the lack in understanding around the consequences of this insertion for one billion of the world’s population, is something that urgently needs to be addressed. This paper attends to this deficit by examining how digital platforms are being designed in respect of the socio-technical setting of informal settlement infrastructures and the consequences for infrastructural change of their insertion. Focusing on four digital platforms deployed within Nairobi’s water and energy infrastructures, the paper builds on the theoretical efforts of urban political ecology framing infrastructures as power laden socio-environmental constructions and goes on to utilise the analytical entry points provided by the notion of heterogeneous infrastructural configurations. The findings identify that, although the digital platforms developed new avenues for infrastructural change via opportunities for utilising data as leverage, they also created fixities for users that caused disjuncture with the natural fluidity that existed within the informal settlements. The findings note that not only do digital platforms reconfigure dynamics of power within heterogeneous infrastructural configurations but they also create opportunities for learning around the intersection of infrastructural flexibility and digital fixities.